Optimal configuration and operation of the regional integrated energy system considering carbon emission and integrated demand response - Zeng, Xianqiang; Wang, Jin; Zhou, Yun; Li, Hengjie (Frontiers in Energy Research, 2023)
Under the "carbon peaking and carbon neutrality" development strategy, in order to suppress load fluctuations and promote renewable energy consumptions in the regional integrated energy system involving concentrating solar power stations, a double-layer optimization model based on the improved NSGA-II algorithm and mixed integer linear programming is proposed. The upper layer completes the capacity configuration process based on multiple objectives to minimize the annual planning cost and the net emission of pollutants. The lower layer is designed to minimize the annual operating cost as well as optimize the output of the devices and the load curves through the participation of the integrated demand response process for flexible loads and the whole process of carbon emissions including carbon capture, carbon utilization, and carbon trading mechanisms to obtain the best operating plan. The final results indicate that the participation of concentrating solar power stations can improve the level of coordinated optimization, and the improved NSGA-II algorithm is stronger than the conventional one in convergent ability and solving accuracy. Besides the optimized process of capacity configuration considering carbon emissions and integrated demand response is capable of improving the economy and environmental protection of the system significantly.